Co Inoculation Effect of Am Fungi and Phosphobacteria on the Growth and Yield of Rhizosphere of Bhendi Abelmoschus esculentus L as Influenced by Chemicals and Biopesticides - Sivakumar, K (International Journal of Pharmaceutical & Biological Archive, 2013)
Co Inoculation Effect of Am Fungi and Phosphobacteria on the Growth and Yield of Rhizosphere of Bhendi Abelmoschus esculentus L as Influenced by Chemicals and Biopesticides